Descending motion of Antarctic stratospheric aerosol layer in winter: Possible effect on stratospheric water vapor budget - Iwasaka, Yasunobu (1986)
P(論文) Lidar measurements at Syowa Station (69°00′S, 39°35′E) revealed that the centroid of aerosol layer descended at the rate of 0.8mm/s during winter. If this motion is a substantial movement of aerosol particles, the mass of water transported into the troposphere is about 5×(10)^7t/winter, and the Antarctic winter stratosphere is an important sink of stratospheric water vapor. If it is a downword air motion carrying small ice crystals, the value is reduced to 5×(10)^4t/winter. departmental bulletin paper